2014
DOI: 10.1016/j.cellsig.2013.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical loading stimulates chondrogenesis via the PKA/CREB-Sox9 and PP2A pathways in chicken micromass cultures

Abstract: Biomechanical stimuli play important roles in the formation of articular cartilage during early foetal life, and optimal mechanical load is a crucial regulatory factor of adult chondrocyte metabolism and function. In this study, we undertook to analyse mechanotransduction pathways during in vitro chondrogenesis. Chondroprogenitor cells isolated from limb buds of 4-day-old chicken embryos were cultivated as high density cell cultures for 6 days. Mechanical stimulation was carried out by a self-designed bioreact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 66 publications
3
88
0
Order By: Relevance
“…Sox9 promoter is known to be regulated by the CREB that binds to a CRE site upstream of Sox9 [30]. We have demonstrated that Sox9 and CREB transcription factors are phosphorylated by PKA during cartilage formation [31,32]. Moreover, a quite complex regulatory mechanism and synergism between Sox9 function and the cAMP-PKA-CREB pathway has been published in both mature and differentiating chondrocytes which includes BMP pathway connections [33].…”
Section: Regulation Of Chondrogenesis Focused On Vip and Pacapmentioning
confidence: 98%
“…Sox9 promoter is known to be regulated by the CREB that binds to a CRE site upstream of Sox9 [30]. We have demonstrated that Sox9 and CREB transcription factors are phosphorylated by PKA during cartilage formation [31,32]. Moreover, a quite complex regulatory mechanism and synergism between Sox9 function and the cAMP-PKA-CREB pathway has been published in both mature and differentiating chondrocytes which includes BMP pathway connections [33].…”
Section: Regulation Of Chondrogenesis Focused On Vip and Pacapmentioning
confidence: 98%
“…Indeed, the addition of PACAP1-38 during oxidative stress prevented the inhibition of cartilage matrix production by normalizing the phosphorylation of Sox9 and CREB in chicken chondrogenic cells [ 13 ]. Recently, the involvement of PACAP or VIP signalling activation in mechanotransduction of developing articular cartilage has been proved by our group [ 68 ] and the importance of PKA in mechanical cellular response was proposed [ 34 ]. Mechanical load of in vitro chondrogenic cell cultures resulted in an increased PAC1 receptor and PACAP expression, and supported the undifferentiated stage of chondroblasts.…”
Section: Pacap and Vip Regulates Chondrogenic Differentiationmentioning
confidence: 98%
“…A moderate level of cyclic mechanical stimulus increases the production of cartilage ECM components and promotes cartilage thickening, 25,26 whereas high levels of mechanical loading induce inflammatory responses, accelerate cartilage degradation, and eventually lead to OA. [27][28][29] In this study, expression of the genes encoding aggrecan and type I and type II collagens were upregulated at cyclic loads of 30-40 psi, but downregulated at 60 and 120 psi (Figure 2(a) and (b)).…”
Section: Discussionmentioning
confidence: 99%